2012
DOI: 10.1001/archophthalmol.2012.1800
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy and Chronic Kidney Disease in the Chronic Renal Insufficiency Cohort (CRIC) Study

Abstract: Objectives Retinal vascular and anatomic abnormalities caused by diabetes, hypertension, and other conditions can be observed directly in the ocular fundus and may reflect severity of chronic renal insufficiency. The purpose of this study was to investigate the association between retinopathy and chronic kidney disease (CKD). Methods In this observational, cross-sectional study, 2605 participants of the Chronic Renal Insufficiency Cohort (CRIC) study, a multi-center study of CKD, were offered participation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
116
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 29 publications
11
116
2
6
Order By: Relevance
“…A detailed description of the CRIC study (7,8) and the methodology used to obtain and interpret retinal images were previously reported (4). All CRIC participants from six CRIC clinical sites in which six fundus cameras were deployed were offered participation in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the CRIC study (7,8) and the methodology used to obtain and interpret retinal images were previously reported (4). All CRIC participants from six CRIC clinical sites in which six fundus cameras were deployed were offered participation in our study.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported a strong independent, cross-sectional association between the severity of retinopathy and the level of kidney dysfunction (4). Previous population studies have shown associations between baseline retinopathy and progression of CKD (5,6).The purpose of this Retinopathy in Chronic Renal Insufficiency (RCRIC) study was to extend these observations by evaluating the relationship between retinal vascular changes and renal disease progression among the well characterized participants enrolled in the Chronic Renal Insufficiency Cohort (CRIC) study, a multicenter, long-term observational, prospective study in patients with CKD (7,8).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, studies have shown that the presence of diabetic retinopathy (DR) itself may leave patients at risk for diabetic nephropathy. [7][8][9][10][11] However, the specific prognostic factors of DR such as DR stage, presence of neovacularization (NV) or vitreous hemorrhage, and degree of nonperfusion area on fluorescein angiography (FA) that predict the progression of CKD have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Retinopathy and nephropathy are most important microvascular complications in patients with diabetes. It is assumed that retinopathy and nephropathy occurs at the same time and that the severity of retinopathy parallels the presence and severity on nephropathy in diabetes mellitus [8,9]. In addition, it is suggested that relationship between renal abnormalities and retinopathy are more frequent in patients with type 1 diabetes than type 2 diabetes [10].…”
Section: Introductionmentioning
confidence: 99%